2008
DOI: 10.1016/j.rmed.2007.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine-induced asthma symptoms correlate with impulse oscillometry but not spirometry

Abstract: Previous studies showed poor correlation between asthma symptoms and spirometric-based bronchial provocation tests. Use of impulse oscillometry (IOS) in airways resistance measurement may be more sensitive. In 20 individuals with stable asthma, we analysed the relationship between methacholine-induced asthma symptoms scores, IOS and spirometry. Following a screening visit, methacholine challenge testing was performed twice (visits 1 and 2). Dyspnoea, tightness and wheeze were quantified using visual analogue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 33 publications
8
50
1
1
Order By: Relevance
“…The latter suggests that the increase in small-airways resistance was responsible for the onset of symptoms in these subjects (Fig 4). 47 These findings are in line with those of Mansur et al, 48 who showed that a higher smallairways reactance is associated with more severe dyspnea, wheezing, and chest tightness after provocation. Together, these studies show that the small airways are involved in BHR and that the response in the small airways is associated with the development of symptoms during a provocation test.…”
Section: Bhr Change Of Small-airways Function During a Provocation Testsupporting
confidence: 87%
“…The latter suggests that the increase in small-airways resistance was responsible for the onset of symptoms in these subjects (Fig 4). 47 These findings are in line with those of Mansur et al, 48 who showed that a higher smallairways reactance is associated with more severe dyspnea, wheezing, and chest tightness after provocation. Together, these studies show that the small airways are involved in BHR and that the response in the small airways is associated with the development of symptoms during a provocation test.…”
Section: Bhr Change Of Small-airways Function During a Provocation Testsupporting
confidence: 87%
“…Mansur et al demonstrated that methacholine-induced symptoms correlated better with changes in R 5 than with change in FEV 1 ; however, all subjects had changes in FEV 1 (54). The present study extends this observation by relating the onset of symptoms to development of isolated changes in oscillometric parameters when FEV 1 did not change.…”
Section: To Evaluate Bhrsupporting
confidence: 78%
“…184 Changes in FOT parameters have been demonstrated when assessing airway responsiveness to bronchodilators and bronchoconstrictors; however, clinically significant changes have not been defined. 185, 186 Similarly, minimal clinically important changes following therapeutic interventions have not been defined. 182 …”
Section: Forced Oscillation Techniquementioning
confidence: 99%